Imobilização de fotocatalisador em fibras eletrofiadas para a degradação do fármaco Paracetamol - Medeiros, Alessandra Ruyz (2022)
In recent times, pharmaceutical compounds have been identified as emerging contaminants for aquatic ecosystems. Thus, this work aims to use the electrospinning technique to obtain polymeric fibers of polybutylene adipate co-terephthalate (PBAT) and cellulose acetate (AC) incorporated with TiO2/g-C3N4, in order to promote the photocatalytic degradation of drug paracetamol (PCT). The polymeric fibers were cross-linked with citric acid in order to increase their stability in water. TiO2/g-C3N4 was synthesized from the chemical modification of TiO2 with g-C3N4. This material was incorporated into the cross-linked polymeric fiber in proportions of 1%, 5% and 10% (m/m) and subjected to photocatalytic degradation tests, with the proportion of 5% (m/m) being chosen for the study due to its higher percentage of drug degradation. The synthesized material TiO2/g-C3N4showed higher photocatalytic potential compared to pure TiO2 and pure g-C3N4, which were 50.5%, 13.1% and 26.1%, respectively. The study of the photocatalytic degradation of PCT was carried out by varying the pH of the medium at 5.0, 7.0 and 9.0, with pH 9.0 being the most efficient, degrading about 86.0% of PCT. The performed HPLC and TOC analyzes of the PCT degradation product showed that the drug degradation is generating by-products. The degradation kinetics for the drug were evaluated and from the results it was obtained that the system follows the pseudo-first order kinetic model. 3 degradation cycles were performed with the polymeric fibers, which showed that they can be reused without having to promote their exchange in a system. Finally, the fibers were characterized by Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA), Fourier Transform Infrared (FTIR), Mechanical Analysis and Contact Angle. Through these analyzes it was possible to identify the incorporation of TiO2/g-C3N4 in the polymeric fibers, as well as their interactions with the polymers, demonstrating changes in thermal stability and improvement in mechanical properties and wettability of the same after crosslinking with citric acid.